Circulating levels of 25-hydroxyvitamin D in relation to hypertension in children and adolescents: a systematic review and dose–response meta-analysis of epidemiologic studies with GRADE assessment - Elahe Mokhtari; Zahra Moradmand; Parisa Rouhani; Parvane Saneei (Journal of Translational Medicine)
Abstract Aims Findings of previous observational investigations about the relation between circulating 25-hydroxyvitamin D (25(OH)D) and hypertension (HTN) in children and adolescents were inconsistent. This systematic review and dose–response meta-analysis summarized the relation between circulating 25(OH)D and childhood HTN in epidemiologic studies. Data synthesis A systematic search of four electronic databases, MEDLINE (PubMed), Web of Science (ISI) and Scopus and Google Scholar was performed up to April 2025. A total of 21 observational investigations that examined the relation of circulating 25(OH)D among children and adolescents and HTN, and reported RRs or ORs with 95% CIs were included. Findings demonstrated that greater circulating 25(OH)D had an association with a 19% decline in odds of HTN (95%CI 0.70, 0.93). Although a significant inverse relation was seen among highest 25(OH)D concentrations and odds of HTN in cross-sectional studies (OR = 0.81; 95% CI 0.69, 0.96), cohorts did not illustrate a significant relation (RR = 0.76; 95% CI 0.52, 1.12). Also, the observed relation of 25(OH)D levels and odds of HTN was significant in non-Asian societies (OR = 0.66; 95% CI 0.53, 0.82), but not in Asian societies (OR = 0.99; 95% CI 0.88, 1.12). Linear dose–response analysis demonstrated that each 25 nmol/L increment in 25(OH)D concentrations was related with a 5% marginal decrease in odds of HTN (OR = 0.95; 95% CI 0.90, 1.01). Furthermore, a significant U-shape nonlinear association was found between 25(OH)D concentrations and HTN. Conclusion In conclusion, greater levels of circulating 25(OH)D levels was linked to a significantly decreased odds of childhood HTN. Moreover, the association was mostly observed in cross-sectional studies and non-Asian countries. Also, non-linear analysis has found a U-shape significant association between circulating 25(OH)D concentrations and HTN in children. The most reduction in odds of HTN was seen in optimum levels of circulating 25(OH)D levels from 35 to 75 nmol/L. Systematic review registration PROSPERO registration no. CRD42022380969. Statement of significance This meta-analysis of epidemiologic studies disclosed an inverse association among circulating 25(OH)D levels and odds of elevated blood pressure among children and adolescents.